Opportunities for optimising care transitions of adults with multiple long-term conditions: a qualitative interview study - Stella Arakelyan; Atul Anand; Stewart W. Mercer; Nazir Lone; Marcus J. Lyall; Julie A. Jacko; Bruce Guthrie (BMC Geriatrics)
Abstract Background The number of adults with multiple long-term conditions (MLTC) who experience frequent care transitions is rising. Improving care transitions for adults MLTC is important because transitions between and within care settings commonly lead to preventable adverse events. We explored multidisciplinary professional perspectives and experiences of managing care transitions for patients with MLTC to identify opportunities for improvement. Methods Qualitative interviews with 30 health and social care professionals in four Scottish integrated Health and Social Care Partnerships. Data were collected between May 2023 and March 2024. Thematic analysis was used, guided by the Sustainable Integrated Chronic Care Models for Multimorbidity: Delivery, Financing, and Performance (SELFIE) framework. Results Care transitions were described as lacking person-centredness and consistency. Variability in decisions on cross-boundary acute care pathways was largely attributed to human factors (e.g., ease of arranging referrals, a lack of trust or awareness of Hospital at Home service) by hospital specialist staff, but to clinical complexity and home environment limitations (physical and social) by community staff. Ineffective interprofessional relationships and poor communication across services were common experiences, significantly driven by a lack of integration between IT systems affecting timely access to information and by services having different priorities and pressures. Workforce shortages, knowledge gaps in managing MLTC, and long-standing capacity issues in social care were identified as important barriers to effectively managing transitions. Conclusions We identified multiple system-level barriers to providing high-quality and safe care transitions. We proposed key improvement opportunities, highlighting the need for using system engineering and systems thinking approaches, underpinned by the active engagement of patients, carers, professionals, and wider stakeholders to drive meaningful and sustainable change in transitions of care.